Genome Silencing and Elimination: Insights from a “Selfish” B Chromosome - Aldrich, John C.; Ferree, Patrick M. (Frontiers in Genetics, 2017)
B chromosomes are non-essential components of numerous plant and animal genomes. Because many of these “extra” chromosomes enhance their own transmission in ways that are detrimental to the rest of the genome, they can be thought of as genomic parasites. An extreme example is a paternally-inherited B chromosome known as Paternal Sex Ratio (PSR), which is found in natural populations of jewel wasp Nasonia vitripennis. In order to ensure its own propagation, PSR severely biases the wasp sex ratio by converting diploid female-destined embryos into transmitting haploid males. This action occurs at the expense of the other paternally inherited chromosomes, which fail to resolve during the first round of division and are thus eliminated. Recent work has revealed that paternal genome elimination by PSR occurs by the disruption of a number of specific histone post-translational modifications, suggesting a central role for chromatin regulation in this phenomenon. In this review, we describe these recent advances in the light of older ones and in the context of what is currently understood about the molecular mechanisms of targeted genome silencing and elimination in other systems.